李長庚海戰詩發微: On Li Changgeng’s Poetry on Sea Battles - 陳, 家煌 (人文中國學報, 2018)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 李長庚（1752—1807），爲乾隆、嘉慶年間水師名將，擅長寫詩，身後留有《李忠毅公遺詩》一部詩集，共收詩百餘首。寫作期間約在乾隆末到嘉慶十二年殉國爲止，期間記録了李長庚海上軍旅生涯及追剿蔡牽的心路歷程。武將擅詩，極爲難得。從李長庚的詩作中，我們得以窺見身爲水師的軍旅生活景況。本文即以李長庚所作的詩，結合當時寫作的時代背景，探討李長庚帶軍追剿海賊蔡牽的甘苦，亦探討他身爲水師統帥的志氣與追剿海賊過程的無奈。李長庚以詩明志，本文則盡量還原當時李長庚的處境，佐以史實記載，以闡述其詩意嘆傷詠嗟之所由，期望以其詩作，見水師大將李長庚海上軍旅生活的個人感慨。 Li Changgeng (1752-1807) was an eminent navy general and poet par excellence who lived through the reigns of Emperors Qianlong and Jiaqing of the Qing (mid 18th-early 19th centuries). He left behind an oeuvre of poetry comprised of more than 100 pieces. These poems are dated from the late Qianlong reign-period to the twelfth year of the Jiaqing reign-period, when Li died as a patriotic martyr. They outline the history and thought of the poet who then served in the navy and on a besiege attack on Cai Qian. It is extremely rare for a navy commander to excel in poetry composition — Li Changgeng wrote about his life in the navy in verse. This present essay examines Li’s poetry by looking into relevant historical backgrounds in an attempt to explore the hardship of his life in his military assault on Cai Qian, as well as his aspiration and helplessness as a naval marshal officer against the pirates. Li wrote poetry as a means by which he expresses his ambitions. This essay is an attempt to restore the veritable historical settings of Li’s time and find the reasons for his sentiments.